To do or not to do with feedback. A study of undergraduate students’ engagement and use of feedback within a portfolio assessment design - Steen-Utheim, A; Hopfenbeck, T (Taylor and Francis, 2018)
Feedback is important for student learning; however, research shows that students can have a number of difficulties when attempting to learn from feedback. Based on an in-depth analysis of undergraduate students’ self-reported reflection logs, we present findings about students’ experiences with oral and written feedback and how they act upon this feedback when a portfolio is the main assessment and learning tool. Our findings indicate that, within our context, students’ overall experiences with receiving feedback are positive. Oral feedback was perceived as particularly valuable to the students while written feedback challenged their understanding. We identified four specific actions the students engaged in to create meaning from the feedback: internal feedback, using oral feedback, initiating dialogue and interacting with peers. The findings indicate that the students take responsibility in the feedback process. The findings are discussed in relation to current perspectives on feedback in higher education.